2019
DOI: 10.1186/s12893-019-0483-y
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative hypocalcemia: analysis of factors influencing early hypocalcemia development following thyroid surgery

Abstract: Background: Early Hypocalcemia is the most frequent complication after thyroid surgery. Several studies have tried to identify factors (patient caracteristics or surgical technique variations) affecting hypocalcemia following thyroid surgery. This studiy evaluates the role of several factors in postoperative hypocalcemia development. Methods: A retrospective study conducted on 2108 patients that underwent thyroid surgery in a single center (1669 women and 439 men). Postoperative early hypocalcemia was defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 33 publications
(60 reference statements)
0
51
0
Order By: Relevance
“…11 Transient hypocalcemia is a common disorder that occurred after thyroid surgery, which is defined as decrease the calcium level below the normal during hospital stay and or recovery within 3 months. 12,13 Some authors concluded that PTH at one hour after thyroid resection whether a partial/subtotal thyroidectomy procedure has a predictive power of 94.4%, respective a specificity of 83.6% with a positive value of prediction of 53%, and a negative value of prediction of 98.7%. 14 Moreover, a combination of PTH and calcium assay might be of more accuracy to indicate the need for replacement of calcium, for instance a value of intact PTH one hour post-operative of higher than 10 pg/mL and a total calcium level of higher than 8.5 mg/dL makes calcium replacement unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…11 Transient hypocalcemia is a common disorder that occurred after thyroid surgery, which is defined as decrease the calcium level below the normal during hospital stay and or recovery within 3 months. 12,13 Some authors concluded that PTH at one hour after thyroid resection whether a partial/subtotal thyroidectomy procedure has a predictive power of 94.4%, respective a specificity of 83.6% with a positive value of prediction of 53%, and a negative value of prediction of 98.7%. 14 Moreover, a combination of PTH and calcium assay might be of more accuracy to indicate the need for replacement of calcium, for instance a value of intact PTH one hour post-operative of higher than 10 pg/mL and a total calcium level of higher than 8.5 mg/dL makes calcium replacement unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to previous studies, which have shown that patients with malignant conditions are more likely to develop hypocalcemia. 2 , 14 …”
Section: Discussionmentioning
confidence: 99%
“… 13 However, other studies have illustrated that malignant conditions were more likely to be associated with a comorbid hypocalcemia. 2 , 14 The plausible underlying mechanism might be related to the attachment and fusion of the thyroid capsule and the parathyroid glands, which might be damaged during CCND. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Post-operative hypocalcaemia has been reported to occur in 23.6% of patients undergoing total thyroidectomy [ 1 ]. As well as causing significant morbidity, hypocalcaemia affects the length of patient stay and necessitates the use of repeated blood tests to guide management [ 5 ]. Therefore, there is a pressing need for surgical technologies that minimise the risk of surgical complications [ 6 ].…”
Section: Introductionmentioning
confidence: 99%